Community archaeology : working ancient Aboriginal wetlands in eastern Australia - Beck, Wendy,; Clarke, Catherine,; Haworth, Robert, (Access archaeology., 2023)
This volume presents the results of an investigation of wetland heritage in eastern Australia, with important contributions to the archaeology of the Tasmanian Midlands and the New England Tablelands.